ФИЗИКА ЎҚИТИШДА ЛАБОРАТОРИЯ ИШЛАРИНИ ЎТКАЗИШ МЕТОДИКАСИ - Айтымбетов, Н.З. (SCIENCE and SOCIETY, 2018)
The article is devoted to the issues of organization and methods of carrying out laboratory work. It contains the information about module technology and pedagogical bases of their use in performing laboratory work.
Keywords: laboratory; theoretical training; practical work; independent work; experience; the teacher